Certification of fisheries human rights and its impact to protecting the rights of fishing vessel crew - Muhammad Nur; M. Hajir Susanto (Legality : Jurnal Ilmiah Hukum, 2021)
The crew of fishing vessels is human beings, the absolute owners of human rights that have been universally recognized. To anticipate and overcome many human rights violations in the Indonesian seas, the Government, through the Ministry of Marine Affairs and Fisheries issued a Regulation of the Minister of Marine Affairs and Fisheries Number 35 of 2015 concerning Fisheries Human Rights Systems and Certification. This research further describes how the provisions of the fisheries' human rights certification and analyzes their impact on protecting human rights for fishing vessel crews in Indonesia. The author uses a normative juridical research method by examining library materials or other secondary materials. The data collection method used is a literature study. The tools used are documents in the form of primary, secondary, and non-legal legal materials. The data obtained were analyzed qualitatively and then presented descriptively. This study found that there are various forms of human rights violations against fishing boat crews. Ministry of Marine Affairs and Fisheries then enforces regulation to prevent human rights violations by business actors against fishing vessel crews. There are several weaknesses in regulations and implementations, namely weaknesses in wage system arrangements, limited regulatory targets, the involvement of workers and employers' representatives in the fisheries human rights team that is not clear, weaknesses of the coordinating system for fisheries human rights teams with supervisors employment, weaknesses of fisheries human rights assessment institutions, weaknesses of socialization for employers and workers. The author suggests that it is necessary to strengthen the coordination and cooperation system between ministries in implementing Fisheries Human Rights Regulations. It also needs to improve communication and dissemination of policies and regulations to stakeholders.